2011
DOI: 10.1152/ajpheart.01279.2010
|View full text |Cite
|
Sign up to set email alerts
|

Acute exercise activates AMPK and eNOS in the mouse aorta

Abstract: Exercise can prevent endothelial cell (EC) dysfunction and atherosclerosis even in the absence of improvements in plasma lipids. However, the mechanisms responsible for these effects are incompletely understood. In this study we examined in mice whether an acute bout of exercise activates enzymes that could prevent EC dysfunction, such as AMP-activated protein kinase (AMPK) and endothelial nitric oxide synthase (eNOS). We also examined whether exercise alters known regulators of these enzymes. C57BL/6 mice und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 57 publications
6
39
0
Order By: Relevance
“…It is known that both metformin and exercise independently activate AMPK. [18][19][20][21] Sharoff et al 17 suggested that it was reasonable to expect little or no additional increase in body insulin sensitivity above baseline values when metformin and exercise were combined. It may be reasonable to assume that the combination of exercise and metformin may have attenuated AMPK in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that both metformin and exercise independently activate AMPK. [18][19][20][21] Sharoff et al 17 suggested that it was reasonable to expect little or no additional increase in body insulin sensitivity above baseline values when metformin and exercise were combined. It may be reasonable to assume that the combination of exercise and metformin may have attenuated AMPK in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently reported that aortic SIRT is activated in response to an acute exhaustive exercise bout without CREB or Akt stimulation. 34,35 In addition, H 2 O 2 , induced by a bout of exercise, has also been found to directly activate pathways leading to mitochondrial biogenesis and macroautophagy. 44,45 The most likely explanation for no change in these targets is that the dose of exercise used in this study acutely stimulated the established AMPK, SIRT, eNOS, CREB and possibly Akt pathways, and that these signalling events returned to baseline over the 24-h from bout to sacrifice.…”
Section: Discussionmentioning
confidence: 99%
“…26,29,59 Lack of a CREB response in any of the models was unexpected but is consistent with a recent study examining acute signalling after a bout of exhaustive exercise. 34 In the SD rats, this may be due to insufficient length or intensity of the intervention; lack of pCREB or CREB response in the SHHF animals may be due to the impaired physiological response to exercise in disease states, such as impaired activation of eNOS or PGC-1α.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the benefits of exercise are widely attributed to its effect on reducing whole-body IR and hyperinsulinemia. Although this explanation, which assumes a systemic effect of exercise on insulin action, still has merit, the discovery in rodents that exercise acutely increases AMPK activity in adipose tissue (40) and aortic endothelium and media (41,42), as well as liver (40) and muscle, raises the possibility that AMPK activation in specific and underappreciated tissues contributes to its beneficial effects. For instance, in rodent aorta, treadmill running increases the activity or expression of 3 known AMPK regulators, LKB1, CAMKKβ, and SIRT1, and it concurrently activates endothelial nitric oxide synthase (eNOS) (41), an enzyme generally thought to protect against atherogenesis in experimental animals (43).…”
Section: Effects Of Exercisementioning
confidence: 99%